Two-Year Longitudinal Changes in Lower Limb Strength and Its Relation to Loss in Function in a Large Cohort of Patients With Duchenne Muscular Dystrophy. (October 2018) - Batra, Abhinandan; Harrington, Ann; Lott, Donovan J.; Willcocks, Rebecca; Senesac, Claudia R.; McGehee, William; Xu, Dandan; Mathur, Sunita; Daniels, Michael J.; Rooney, William D.; Forbes, Sean C.; Triplett, William; et al.
Abstract : Objective: The main objective of this study was to examine the effect of disease on strength in two functionally important lower limb muscles for a period of 2 yrs in children with Duchene muscular dystrophy. Design: Seventy-seven Duchene muscular dystrophy children participated in this study. Plantar flexors, knee extensors, strength, and performance on timed tests (6-min walk, 4-stairs, 10-m walk, supine-up) were assessed yearly for 2 yrs. Multivariate normal regression was used to assess changes in strength over time in the Duchene muscular dystrophy group. Spearman correlations were computed to examine relationship between strength and function. Results: Normalized plantar flexor and knee extensor strength showed a significant decrease ( P < 0.05) over 2 yrs, with larger declines in knee extensor. At baseline, knee extensor strongly correlated with performance on timed tests. However, plantar flexor strength was found to be a stronger predictor of loss in ambulatory function. Modest correlations ( r = 0.19–0.34) were found between the decline in strength and functional performance over 2 yrs. Conclusions: This study describes the loss of lower limb strength in a large cohort of Duchene muscular dystrophy children for 2 yrs. The findings support that lower limb strength alone cannot account for the decline in performance on functional tests, and the role of other contributing factors, such as compensatory strategies, should be considered.